MANAJEMEN BANDWIDTH MENGGUNAKAN METODE RADIUS SERVER - RIZKIANA, WIKI INDAH RIZKIANA; SUNARSAN SITOHANG (LPPM Universitas Putera Batam, 2025)
Internet needs are increasing and complex in terms of taking up bandwidth by activities on one or several clients who carry out activities such as downloading or uploading files to high-quality video streaming functions is one of the causes of loss of bandwidth. Good bandwidth management is needed to ensure the network runs efficiently, one way is to use MikroTik through the radius authentication method. Radius (Remote Authentication Dial-In User Service) is a network protocol used to perform authentication, authorization, and accounting (AAA) on networks that use wireless network connections or internet connections. The use of the Radius Authentication method in implementing bandwidth management on MikroTik also allows network administrators to secure the network from unwanted users. every user can use the internet with a predetermined bandwidth and the radius server works well in carrying out its duties. The conclusion is that the use of the radius server method has succeeded and resulted in a network that is more efficient in bandwidth management.